Trends and patterns of federal government spending in Malaysia - M. Mithani, Dawood; Hassan, Sallahuddin; Chik, Abdul Razak (Universiti Utara Malaysia, 1998)
This paper reviews the growth and composition of Federal Government spending in Malaysia during the Post-New Economic Policy era, with a comprehensive approach and analytical outlook. Between 1970 and 1997 the compound annual growth rate of total government expenditure was estimated at 11.3 percent. During the 1970s and 1980s, a fiscal imbalance in expenditure pattern emerged as a result of excessive growth in operating expenditure against that of developing expenditure. Government spending as percentage of GNP declinedfvom 34.1 percent in 1990 to 20.3 percent in 1997. In a relative sense, this suggests that Malaysia currently has the smallest government involvement, even compared to Japan and the USA's market-oriented mixed economies. The expenditure pattern and policy of the Malaysian government reveals its real concern for the social sector development and eradication of poverty, besides sound fiscal fundamentals contained in surplus budgets in recent years. Our study, however, suggests that economizing in government spending is more important than budgetary curtailment. The government should appoint an advisory Public Expenditure Committee, and publish a 'White Paper' on spending programmes on a regular basis. The fiscal management may further be improved by incorporating 'rolling expenditure programming' in the budgetary implementation. The on-going fiscal reforms should be made more effective to establish a prudent government sector with enhanced efficiency and productivity.